Determinants of Audit Report Lag with Intervening Auditor Specialist Industry - Yudhi Prasetiyo (Politeknik Negeri Madiun, 2023)
This research was conducted to test and determine the factors that affect audit report lag. There are two independent variables in this study, namely profitability which is proxied by return on investment, and company size, which is indicated by total assets, then there is an industry specialist auditor as intervening. The research method applied in this research is quantitative by using Sem Partial Least Square and using Smart PLS 3.0 software as a data processing tool. The sample used in this study is a publicly listed BUMN company consistently during the 2014-2021 period. The results found in this study are that the profit proxied in return on investment does not affect audit report lag and industry specialist auditors, then company size has an influence on audit report lag but there is no relationship with industry specialist auditors, then industry specialist.